Restoration of boreal peatland impacted by an in‐situ oil sands well‐pad 1: Vegetation response. Issue 3 (7th September 2021) - Xu, Bin; Rochefort, Line; Bird, Melanie; Khadka, Bhupesh; Strack, Maria
Abstract : In this study, our goal was to adapt the moss layer transfer technique (MLTT), first developed to restore degraded Sphagnum ‐dominated peatland explicitly with a bryophyte layer, to a former in‐situ oil sands well‐pad constructed with nearby mineral fill in northwestern Alberta, Canada. Mineral fill was either completely removed or partially removed with residual fill buried under excavated and decompacted peat, followed by the transfer of donor moss collected from nearby linear features with different plant communities in peatlands. Three years after MLTT, peatland vegetation covers 63% of the site. Carex spp. dominate with 36% coverage, followed by mosses at 12%, including 3% Sphagnum spp. and 8% fen mosses, and shrubs at 8%. Different substrate adjustment treatments and types of donor moss had negligible impact on vegetation development although areas without MLTT remained devoid of mosses and had the lowest peatland species cover. Instead, surface elevation, moisture conditions, and substrate chemistry played important roles in shaping the vegetation communities. The prompt introduction and establishment of peatland donor species through MLTT was crucial to the overall re‐establishment of peatland vegetation. This is the first full pad scale study to prove that a flat, moist peat surface created by the removal and/or burial of mineral fill can support peatland vegetation development, particularly ground layer bryophytes. Overall, the reclaimed well‐pad appears to be on trajectory toward becoming a functional peatland and our approaches should be considered and tested in future well‐pad reclamation trials.